# CONDITIONAL IDENTITIES TRIGONOMETRIC EXAMPLES

Trigonometric identities are true for all admissible values of the angle involved. There are some trigonometric identities which satisfy the given additional conditions. Such identities are called conditional trigonometric identities.

Here we are going to see some examples to show how to solve conditional trigonometric identities problems.

Example 1 :

If A + B + C  =  180°, prove that

tan(A/2)tan(B/2) + tan(B/2)tan(C/2) + tan(C/2)tan(A/2) = 1

Solution :

A + B + C  =  180

A + B  =  180 - C

A/2 + B/2  =  90 - C/2

tan(A/2 + B/2)  =  tan[90 - (C/2)]

tan(A/2 + B/2)  =  cot(C/2) -----(1)

Formula :

tan(A + B)  =  tan A + tan B / (1 - tan A tan B)

Use the above formula on the left side of (1).

(1)----->

[tan(A/2) + tan(B/2)] / [(1 - tan(A/2)tan(B/2)]  =  1/tan(C/2)

Take reciprocal on both sides

[1 - tan(A/2)tan(B/2)] / [tan(A/2) + tan(B/2)]  = tan (C/2)

1 - tan(A/2)tan(B/2)  =  tan(C/2)[tan(A/2) + tan(B/2)]

1 - tan(A/2)tan(B/2) = tan(A/2)tan(C/2)+tan(B/2)tan(C/2)

1  =  tan(A/2)tan(C/2)+tan(B/2)tan(C/2)+tan(A/2)tan(B/2)

Example 2 :

If A + B + C  =  180°, prove that

sinA + sinB + sinC  =  4cos A/2 cos B/2 cos C/2

Solution :

sinA + sinB + sinC :

=  2sin(A + B)/2cos(A - B)/2 + sinC

=  2sin(180 - C)/2 cos (A - B)/2 + sin C

=  2 sin C/2 cos (A - B)/2 + 2 sin C/2 cos C/2

=  2 sin C/2 [cos (A - B)/2 + sin C/2]

=  2 sin C/2 [cos (A-B)/2 + sin (180-(A+B))/2]

=  2 sin C/2 [cos (A-B)/2 + sin (90-(A+B)/2)]

=  2 sin C/2 [cos (A-B)/2 + cos (A+B)/2]

=  2 sin C/2 [2 cos A/2 cos B/2]

=  4 cos A/2 cos B/2 sin C/2

Example 3 :

If A + B + C  =  180°, prove that

sin(B + C - A) + sin(C + A − B) + sin(A + B - C) = 4sinAsinB sinC.

Solution :

A + B + C  =  180

 A + B  =  180 - C B + C  =  180 - A C + A  =  180 - B

sin(B + C - A) + sin(C + A - B) + sin(A + B - C) :

=  sin(180 - A - A) + sin(180 - B - B) + sin(180 - C - C)

=  sin(180 - 2A) + sin(180 - 2B) + sin(180 - 2C)

=  sin 2A + sin 2B + sin 2C

=  2sin(A + B)cos(A - B) + sin2C

=  2sin(180 - C)cos(A - B) + 2sinCcosC

=  2sinCcos(A - B) + 2sinCcosC

=  2sinC[cos(A - B) + cosC]

=  2sinC[cos(A - B) + cos(180 - (A + B)]

=  2sinC[cos(A - B) - cos(A + B)]

=  2sinC[-2sinAsin(-B)]

=  4sinCsinAsinB

=  4sinAsinBsinC

Apart from the stuff given above, if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

## Recent Articles

1. ### SAT Math Videos

May 22, 24 06:32 AM

SAT Math Videos (Part 1 - No Calculator)

2. ### Simplifying Algebraic Expressions with Fractional Coefficients

May 17, 24 08:12 AM

Simplifying Algebraic Expressions with Fractional Coefficients